OPTIMIZATION OF SILICA EXTRACTION OF RICE HUSK (Oryza sativa L.) TO INCREASE ABSORPTION PLANT NUTRIENTS - Dina Wahyu Indriani; Nunun Barunawati; S H Sumarlan (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Brawijaya, 2018)
Extraction of silica has now been developed as one of the additional nutrients in the soil. This silica extraction technology is developed from materials that are no longer used as an example of rice husks. As a result of the extraction of rice husk silica is used to nourish the rice plants themselves. The addition of plant nutrients can be optimized by using an encapsulation system. The process of nutritional encapsulation is expected to optimize the absorption of nutrients in the soil in slow reaction. This inhibitory process can also be supported by the use of nutrient remobilization. So the purpose of this research is to obtain the optimum result of silica extract from rice husk and to know the characteristics of capsulation result of silica extract produced. As for this research using the addition of KOH so that this research method using Randomized Block Design (RBD) with KOH 2.5%, 5%, and 7.5%. The analyst has performed mass equilibrium analysis, water content of the material, and SEM analysis for physical analysis. In this study showed that with the addition of 5% KOH treatment to be the best treatment in this study that produced as many as 4.5 grams. Furthermore, the sample was treated with liquid nitrogen as an encapsulation medium. The result of the research showed that the silica value contained in the extract yield on KOH 5% by 19.4% while in addition KOH 7.5% silica content of 21.8%. This shows the highest value of yield that is in the addition of KOH of 5% but the silk content of the most that is in the addition of KOH of 7.5%.